Long-term risk of chronic kidney disease in living kidney donors at a single center in Thailand - Wongvittavas, Non; Opanuraks, Julin; Panumatrassamee, Kamol; Bunyaratavej, Chanatee; Tantiwongse, Kavirach; Ratchanon, Supoj; Santi-ngamkun, Apirak; Prasopsanti, Kriangsak (Chulalongkorn Medical Journal, 2023)
Background : Although the results of several studies support the safety of live kidney donation, there is no functional deterioration, some donors have proteinuria and hypertension (HT). Most of the studies were done in Europe and America, in Asia, however, the information about donors living with one kidney is lacking. Objective : To study the long-term risks of chronic kidney disease (CKD) in living kidney donors at one medical center in Thailand. Design : A retrospective study. Setting : Division of Urology, Department of Surgery, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand. Materials and Methods : Donors who were followed up for more than 1 year after nephrectomy were included. We assessed each donor’s blood pressure, urine protein, and estimated glomerular filtration rate (eGFR). Results : The donors had a mean age of 37.5 ± 9.78 years at donation. The median follow-up period was 3.62 years (range 1 - 11 yrs ). There were statistically significant increases in SBP from 113.3 ± 11.15 to 120.5 ± 11.99 mm Hg. and BMI from 22.9 to 23.6 (P <0.001). 4 (4.7%) developed hypertension and 2 (2.3%) displayed proteinuria. Serum Cr significantly changed from 0.72 ± 0.2 to 1.02 ± 0.22 mg/dL. (P <0.001) and eGFR from 114.6 ± 36.62 to 74.26 ± 14.46 mL/min/1.73 m2. (P <0.001) 5(5.8%) had CKD (eGFR<60 mL/min/1.73 m2). After transplantation, eGFR decreased by < 1 mL/min/1.73 m2 each year. Age at donation and longer follow-up time were significant risk factors for renal functional deterioration (CKD, HT, proteinuria) (P = 0.04, OR = 1.092 (1.004 - 1.188) and P = 0.012, OR = 1.425 (1.079 - 1.881), respectively). Conclusion : Renal function was well preserved after donor nephrectomy in early period. A significant proportion of living donors might develop renal deterioration upon long-term follow-up.